Utilization of Game-Based Learning Media in Enhancing Student Interest in Physical Education Learning - Anggraini, Dhea Reni; Syahbana, Muhammad Ali; Marpaung, Mawar Humairoh; Nst, Dewi Sartika; Mendrofa, Rivaldin; Pertiwi, Dinda Nano (Pusdikra-Publishing.com, 2025)
This study investigates the use of game-based learning media to enhance students' interest in Physical Education (PE). With the growing need for innovative teaching methods to engage students, game-based media is considered an effective tool to improve motivation and learning outcomes. The research was conducted with high school students at MAN 1 Medan, where they were exposed to game-based learning for eight weeks. Data were collected through questionnaires to assess changes in student interest before and after the intervention. The results showed a significant increase in students' interest in PE (p < 0.05) after using game-based learning media. This indicates that incorporating games into PE lessons can make learning more engaging and enjoyable, leading to greater student participation and improved learning experiences. Furthermore, the study found that game-based learning also fostered improved social skills and teamwork among students. Despite some challenges, such as technical difficulties and limited practice time, the findings suggest that game-based learning is a promising approach to enhance the quality of PE instruction. The study recommends further development and integration of game-based media into the PE curriculum to provide more interactive and effective learning opportunities.